Analysis of the Influence of Multimedia Information Fusion on the Psychological Emotion of Financial Investment Customers under the Background of e-Commerce - Tehong Zhu (Advances in Multimedia)
With the gradual deepening of the research on financial investment, some data show that investors’ limited rationality and self-psychological emotions do not always seek to maximize their own interests when making investment decisions, but lead to investment failure due to the influence of their bad psychological emotions. With the rise of e-commerce and the development of multimedia, multimedia information fusion and presentation are realized, and multiple terminals interact with each other in real time and effectively. It is in this context that this paper analyzes the impact of multimedia information fusion on the psychological emotions of financial investment customers in the context of e-commerce and formulates a correct and effective investment plan in line with financial investment customers. The results of the experiment are as follows: (1) the background of the current e-commerce development, the principle of multimedia information fusion, and the problems existing in the emotional impact of financial investment customers are analyzed, the research direction of the experiment is determined, and the target problem is analyzed according to the information fusion technology, which provides technical support for the research of this paper. (2) Among the existing multimedia information fusion design algorithms, Mgr fusion algorithm, advanced MCR fusion algorithm, multimodal fusion reordering algorithm, and trust function algorithm are introduced to compress and analyze the complex multimedia data information in different fields, which not only shortens the time required for a large amount of data information fusion. And The emotional data information of financial investment customers is efficiently counted and classified.